The Effect of Workload, Work Stress and Work-Life Balance On Employee Performance (Case Study On Startup Employees In Jakarta) - Mufida Ahmad, Alfi; Handaru, Agung Wahyu; Usman, Osly (Green Publisher Indonesia, 2022)
In order to ultimately boost business earnings, this study tries to ascertain the impact of workload, work stress, and work-life balance on employee performance. Descriptive quantitative research methodology is employed. This study used an unlimited number of startup employees in Jakarta as its population. The nonprobability sampling approach is employed in the sampling procedure. According to the research's findings, employee performance among startup workers in Jakarta is significantly improved by workload. Because of this, the company's performance expectations will not be met the more work the employees feel they are expected to do. Workload significantly influences how stressed out startup employees in Jakarta feel at work. Thus, employees experience more stress the more work they have to do. Work-life balance for startup employees in Jakarta is significantly impacted by workload. As a result, employees feel less of a work-life balance as their burden increases. Workplace stress significantly affects startup employees' productivity in Jakarta. Employee performance suffers as a result of increased work stress. Work-life balance significantly influences how well startup employees in Jakarta perform at work. Therefore, the greater the employee's success for the organization, the better the ability to manage work and personal life. Work-life balance is significantly impacted by work stress for startup employees in Jakarta. Therefore, the employee would experience less stress the better he can balance his life. work stress and workload have a significant effect on employee performance. this means that the amount of burden and stress felt by employees causes employee performance to decrease. workload, work stress have a significant effect on work-life balance. this means that workload and work stress will be reduced when employees can balance their lives. workload, work life balance has a significant effect on employee performance. This means that the demands of work will cause difficulties for employees to balance between personal life and work life. Work-life balance is significantly impacted by workload and workplace stress. Employees will perform better when they can balance their personal and professional life, which will lessen work-related stress. workload, work stress and work life balance affect performance. this means that workload and work stress will decrease when employees can balance their lives so that employees will improve their performance.